Are changes in breeding habitat responsible for recent population changes of long-distance migrant birds?. Issue 2 (2nd April 2016) - Mallord, John W.; Smith, Ken W.; Bellamy, Paul E.; Charman, Elisabeth C.; Gregory, Richard D.
ABSTRACT: Capsule: The direction and magnitude of changes in structure of UK woodlands since the 1980s, are inconsistent with them playing a causative role in the declines of four migrant bird species in upland oak woods. Aims: To investigate whether changes in woodland structure were a possible cause of population changes of four Afro-Palearctic migrants (Wood Warbler Phylloscopus sibilatrix, Tree Pipit Anthus trivialis, Pied Flycatcher Ficedula hypoleuca and Common Redstart Phoenicurus phoenicurus ) in the upland oakwoods of western and northern Britain. Methods: Bird population estimates and measures of woodland structure were recorded in two time periods 1982–85 and 2003–04 across six regions of the UK. We modelled the effect of habitat change and initial habitat state on population changes between the two time periods. The predicted effects of habitat change on populations were then compared with observed population changes across the different regions. Results: All four species underwent population declines; there were also significant increases in ground cover and understorey cover. The number of birds in 2003–04 was influenced by habitat structure at this time in addition to showing regional differences. Change in bird numbers varied between regions and was affected by both the initial habitat state and change in habitat structure, with regional variation in the effect of habitat change. There was however no relationship between the predicted effect of change in habitat structure on population size and observed regional population changes. Conclusions: Changes in woodland structure are unlikely to be the main driver of population change in these four migrant bird species, and large-scale factors affecting demographics in other parts of their breeding range or in their wintering areas are likely reasons for local population declines.